2010
DOI: 10.1093/ejo/cjq042
|View full text |Cite
|
Sign up to set email alerts
|

Altered oral sensory perception in tongue thrusters with an anterior open bite

Abstract: The aim of this study was to evaluate oral sensory perception in patients with an anterior open bite (AOB) and associated tongue thrusting activity. This study was performed in the Department of Orthodontics, Government Dental Hospital, Chennai, on 30 subjects (16 females and 14 males) aged from 12 to 17 years with an AOB associated with a tongue thrust and in a control group of 100 subjects (53 females and 47 males aged from 12 to 17 years) with a normal occlusion and no oral habits. Stereognosis and two-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…However, this conflicts with the findings of Premkumar et al who noted a high percentage of errors in identification of surface texture in subjects with an anterior open bite 14 . Errors in density identification were intermediate to the errors in shape and texture identification in this study.…”
Section: Discussion:-contrasting
confidence: 85%
See 2 more Smart Citations
“…However, this conflicts with the findings of Premkumar et al who noted a high percentage of errors in identification of surface texture in subjects with an anterior open bite 14 . Errors in density identification were intermediate to the errors in shape and texture identification in this study.…”
Section: Discussion:-contrasting
confidence: 85%
“…Therefore, even if one cannot infer skeletal pattern per se as the sole cause of AOB, the persistent presence of a physical barrier in the form of the tongue preventing incisors from coming into an ideal vertical relationship may possibly be responsible for diminished oral sensory perception in the SAOB subjects. Previous research has also demonstrated a statistically significant inferior sensory ability to perceive shapes and texture in AOB subjects associated with a tongue thrust 14 . In our study, though the response time of the SAOB subjects was longer than the control subjects, the differences were however statistically not significant.…”
Section: Discussion:-mentioning
confidence: 89%
See 1 more Smart Citation
“…Cutaneous sensitivity tests are used to detect reduced sensory perception and to diagnose neuropathies and abnormalities of sensory function 18,30,31 . The TPD test is commonly used to assess upper limbs and airways cutaneous perception in several populations [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The TPD test is commonly used to assess upper limbs and airways cutaneous perception in several populations [30][31][32][33] . Nylon monofilaments and the diapason test pitch have been used most often in the sensitivity evaluation of the lower limbs 11,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%